THE ANALYSIS OF A CERTAIN TECHNIQUE THAT IMPACTS ON THE QUALITY OF TRANSLATION IN THE STATEMENT OF RESPONDING TOWARD ARGUING SPEECH ACT IN THE NOVEL ALLEGIANT - Siti Fathiyatus Sholihah; M.R. Nababan; D. Djatmika (Universitas Sebelas Maret, 2018)
ABSTRACT This research discusses about how a certain technique can impact on the quality of translation in the statements of responding toward arguing speech act. It aims to determine the impact of choosing a certain micro technique of translation toward the quality in terms of accuracy, acceptability, and readability. This research can be classified as a descriptive qualitative research which focuses on a single case. The source data of this research is the novel Allegiant, its translation in Indonesian, and the two raters. Then, the data are collected from the statement that responds toward arguing. Furthermore, Focus Group Discussion that has been done by two raters and the researcher is used to assess the three aspects of translation quality and determine the micro technique that has been applied to translate the statement that responds arguing speech act. The result of this research is that the application of micro technique of translation that is mostly applied is established equivalent technique that has been applied 172 data 52,9 % that has been influenced the quality of translation because he total average of quality translation is 2,97 that is considered as a good translation. In other words, the establish equivalent has a good impact toward quality of translation toward statement that responds of arguing speech act.